Uzbrojenie z cmentarzyska kultury luboszyckiej w Sadzarzewicach, pow. Krosno Odrzańskie - Andrzejewska, Agata; Demkowicz, Karol (Acta Universitatis Lodziensis. Folia Archaeologica, 2017)
The cemetery in Sadzarzewice (former Sadersdorf) is one of the most important archaeological sites in Lower Lusatia and it dates back to the pre-Roman and Roman iron ages. It was included into the Luboszyce culture by Grzegorz Domański in his work from 1979. Along with two other cemeteries, located nearby in Grabice and Luboszyce, the Sadzarzewice complex constitutes the oldest chronological horizon of this taxonomic group, and the region is regarded as the starting point of its later expansion. Despite the site’s great significance for the prehistory studies of the Oder basin, its state of study is far from satisfactory. This is mostly due to the fact it was discovered and explored at the end of the XIXth century, that is in the time archaeological methods were still in development. Further complication was caused by the history of the region – nearly all of the artifacts were lost during WWII, and as an effect, the cemetery’s inventory is known only from a publication dating back to 1895. Nevertheless, during my research for my dissertation on the armament of the Luboszyce culture, I managed to identify a couple of those lost finds. This small group consisted of an ornamented spearhead, an untypical javelin- or arrowhead, and a shield grip. The total number of Roman iron age weapon and equestrian equipment finds from the cemetery is 41 – 4 swords, 2 sword scabbard belt loops, 2 axes, 6 spearheads, 2 javelin heads, 7 arrowheads, 4 shield bosses, 2 shield grips and 12 spurs. The artifacts from Sadzarzewice fit into the phase B2b–C2 (late 2nd–3rd cent. A.D.) range. Those weapons that were possible to date with considerable precision can be situated within the phase C1, some even can be as old as B2b, although there is no certain evidence of such early chronology. Another notable feature of the Sadzarzewice artifacts is the evidence of various interregional influences – either from the West (the Elbian circle) and East (the Wielbark and Przeworsk cultures) which phenomenon, although characteristic for the Luboszyce culture in general, is best observed in the early stages of this unit’s development.